Exact Wirelength of Embedding Locally Twisted Cube into Rooted Hypertree - Shalini, M Arul Jeya; Sakthishwari, S; Abraham, Jessie (International Journal of Computer Sciences and Engineering, 2025)
The performance ability of a distributed multiprocessor is determined by its corresponding interconnection network and the primary criteria for choosing an appropriate interconnection network is its graph embedding capability. An embedding of a graph into a graph is an injective map on the vertices such that each edge of is mapped into a shortest path of . The wirelength of this embedding is the sum of the number of paths corresponding to crossing every edge in . In this paper we embed the locally twisted cube into rooted hypertrees to obtain the exact wirelength.